Synthesis and research of reactivation of phosphorylated cholinesterase by quaternary pyridinium-aldoxime salts - Bobkova, Ludmila (Publishing House of Lviv Polytechnic National University, 2015)
The interaction of pyridine-4(-3,-2)aldoxime has been studied whit 3-bromo-N,N,N-trialkyl-2-oxo(-hydroxyimino)-1-propanaminium bromide. The structure of all synthesized compounds was determined by elemental analysis as well as by physical and chemical methods. All synthesized compounds were tested for reactivation of phosphorylated acetylcholinesterase. Using fragments of the molecules (an oxime group, 3-bromo-N,N,N-trimethyl(or triethyl)ammonium [(orN-methylmorpholinium)-2-oxo(or 2-hydroxyimino)]propan bromides), a new series of pyridinium-aldoxime salt (cholinesterasereactivator) was obtained. Вивчена взаємодія піридин-4(-3,-2)аль-доксиму із 3-бром-N,N,N-тріалкіл-2-оксо(-гідроксіміно)-1-пропанамоній броміду. Склад і структура синтезованих сполук 4(-2,-3)-(гідроксімінометил)-1-[(2¢-оксо(гідроксіміно)-¢-ріалкіламоній)пропіл)]піридиній дибромідів встановлені з використанням елементного аналізу, фізичних та хімічних методів. Синтезовані сполуки випробувані на їх активність як реактиватори фосфорильованої ацетилхолінестерази. З використанням молекулярних фрагментів (оксимна група, 3-бром-N,N,N-тріметил(або тріетил)амоній(або N-метил-морфоліній)-2-оксо(або 2-гідроксіміно)пропан броміди), отримані нові реактиватори холінестерази в ряду солей піридину.
Синтез і дослідження реактивації фосфорильованої холінестерази четвертинними солями піридиній-альдоксиму
Keywords: synthesis; quaternary pyridinium-aldoxime salt; cholinesterase reactivator; синтез; четвертинна сіль піридиній-альдоксиму; реактиватор фосфорильованої ацетилхолінестерази